2018
DOI: 10.1021/acscatal.8b00696
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Bismuth Molybdates for Selective Oxidation of Propylene Probed by Correlative Operando Spectroscopies

Abstract: MoO 6 as target bismuth molybdate phases were prepared by hydrothermal synthesis and flame spray pyrolysis and tested for their catalytic performance in the selective oxidation of propylene. Their structure and reactivity during temperature-programmed reaction (TPR) and under reaction conditions were investigated by in situ and operando X-ray absorption spectroscopy (XAS), X-ray diffraction (XRD), and Raman spectroscopy. To gain insight into amorphous and crystalline structures at the same time, XAS and XRD as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
2
35
0
Order By: Relevance
“…The preparation of the two-component catalyst system HS: α-Bi 2 Mo 3 O 12 is described elsewhere. [44]…”
Section: Catalyst Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of the two-component catalyst system HS: α-Bi 2 Mo 3 O 12 is described elsewhere. [44]…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The setup for evaluation of the catalytic performance is described in detail in the literature. [44] The hydrothermally-prepared and subsequently calcined catalyst HS: BiÀ MoÀ CoÀ Fe oxide was ground, pressed and sieved to give a fraction of 300-450 μm. 800 mg of the catalyst were placed in a quartz tubular reactor (6 mm inner diameter).…”
Section: Catalytic Performance Testsmentioning
confidence: 99%
“…Catalysts used for this process are typically multicomponent systems based on bismuth molybdate phases [3][4][5][6]. Recent studies have shown that such bismuth molybdates are accessible through a variety of novel synthesis methods [7][8][9][10][11][12], the choice of which can exert a strong influence on catalyst activity and performance [13]. In this context, flame spray pyrolysis (FSP) has proven to be an attractive method for the synthesis of metal oxide catalysts [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The complete change in beamline configuration to jump from one edge to another one takes one minute in the worst case and 30 s generally. This "edge jumping" feature is highly demanded [4][5][6][7] as it provides multiple edge characterization on a material evolving under working conditions (temperature, pressure, or gas composition for catalysis, applied current or potential for energy related materials) in a single experiment. In this way, the experimentalist has a true depiction of the concomitant temporal evolutions of the different active centers subjected to exactly the same operating conditions.…”
mentioning
confidence: 99%
“…As a result, the photons density impinging the sample can be adjusted by a factor 100, which is of paramount importance for samples suffering from radiation damage, without altering the signal-tonoise ratio since the photon flux is preserved [3]. This versatility in beam size also allows accommodating different sample environments, such as large Lytle-type cells [2] or thin capillary reactors [7].…”
mentioning
confidence: 99%